Exploring Multicultural Education: A Case Study of Singkawang - Buwono, Sri; Queiroz, Carla; Karolina, Venny; Xaixanith, Toby (International Journal of Educational Research & Social Sciences, 2023)
This article investigates multicultural education in Singkawang, Indonesia, where diverse ethnicities coexist. Rapid social changes often trigger ethnic migration, leading to a convergence of cultures. Ethnocentrism can impede inter-ethnic communication, fostering stereotypes and ethnic conflicts. Multicultural education, emphasizing democratic, humanistic, and pluralistic values, is proposed to address these issues. Singkawang, recognized for its ethnic diversity, serves as a unique case study. The research method involves qualitative analysis with interviews from students, teachers, and parents from various ethnic backgrounds. Findings revealed the city's friendly atmosphere, preserved harmony, and respectful behavior, especially among students. "Ngopi bareng" (coffee gathering) is identified as a key practice among adult localsstated by parents of students in maintaining multiculturalism. Schools also actively promote tolerance through democratic practices, curriculum diversity, and inclusive instructional strategies. The article concludes that multicultural education is vital in fostering acceptance, understanding, and appreciation of diversity, emphasizing the dynamic nature of this approach in shaping open-minded individuals in a diverse society. Further research is recommended to explore this topic's nuances.